Do labor costs affect companies' demand for labor? - Daniel S. Hamermesh (IZA World of Labor, 2021)
Higher labor costs (higher wage rates and employee benefits) make workers better off, but they can reduce companies' profits, the number of jobs, and the hours each person works. The minimum wage, overtime pay, payroll taxes, and hiring subsidies are just a few of the policies that affect labor costs. Policies that increase labor costs can substantially affect both employment and hours, in individual companies as well as in the overall economy.
Keywords: J20; J23; 330; labor demand; wages; employee benefits